2008
DOI: 10.1103/physrevlett.101.085005
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Complete Finite-Larmor-Radius Stabilization in Extended MHD

Abstract: The dominant finite-Larmour-radius (FLR) stabilization effects on interchange instability can be retained by taking into account the ion gyroviscosity or the generalized Ohm's law in an extended MHD model. However, recent simulations and theoretical calculations indicate that complete FLR stabilization of the interchange mode may not be attainable by ion gyroviscosity or the two-fluid effect alone in the framework of extended MHD. For a class of plasma equilibria in certain finite-beta or nonisentropic regimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…The previous investigations of the magnetic RT instability and nonlinear structures of flute waves were restricted to the long wavelength limit when the wave spatial scale is larger than the ion Larmor radius. Therefore, the conclusions [4,5] on the possible absence of complete FLR stabilization in the wavelength region where the equations are not applicable, remained doubtful. Recently, in order to overcome this difficulty, the theory of flute waves, driven by the RT instability, was extended to the case of arbitrary spatial scales [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous investigations of the magnetic RT instability and nonlinear structures of flute waves were restricted to the long wavelength limit when the wave spatial scale is larger than the ion Larmor radius. Therefore, the conclusions [4,5] on the possible absence of complete FLR stabilization in the wavelength region where the equations are not applicable, remained doubtful. Recently, in order to overcome this difficulty, the theory of flute waves, driven by the RT instability, was extended to the case of arbitrary spatial scales [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…About 50 years ago it was shown [1][2][3] that the finite Larmor radius (FLR) effects have a stabilizing influence on this instability. However, the subsequent numerical simulations and detailed theoretical investigations [4,5] showed that complete FLR stabilization is not always attainable. The previous investigations of the magnetic RT instability and nonlinear structures of flute waves were restricted to the long wavelength limit when the wave spatial scale is larger than the ion Larmor radius.…”
Section: Introductionmentioning
confidence: 99%
“…The extended MHD equations have been widely used to study interchange instability, because they are able to be applied to the complicated magnetic confined closed systems. 6,7 The FLR effects on an interchange instability are also important in an open system such as a tandem mirror. [8][9][10][11][12] The generalized Ohm's law and gyroviscosity in the extended MHD equation were derived theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…5,13 Recently, it has been reported that the complete FLR stabilization of the interchange mode may not be attainable by the gyroviscosity or generalized Ohm's law alone in the frame work of extended MHD. 7 The stability boundary of an interchange instability with FLR was determined by the kinetic analysis. 4,14 Thus, it is worth verifying with the help of a particle simulation that the interchange instability can be really stabilized by FLR effects completely.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al have shown that the complete stabilization is absent for a certain b-value (ratio of the thermal pressure to the magnetic pressure), though the growth rate at high wave numbers are reduced significantly. 9 More recently, Xi et al have shown for the ion density gradient mode of magnetically confined plasma 10 and the authors have shown for the R-T mode 11 independently that the high modes can be stabilized by the combination of the two-fluid and the gyro-viscous terms, not by only one of them. It has been also shown in Ref.…”
Section: Introductionmentioning
confidence: 99%